Will Robie : The Innocent - Book 1 - Baldacci, David; McLarty, Ron.; Cassidy, Orlagh (New York, NY Hachette Audio, 2012)
Will Robie, a freelance hitman working for the government, rescues a teenage girl whose parents' disappearance may be linked to a vast, high-level cover-up.
Unabridged.
Compact discs.
Read by Ron McLarty with Orlagh Cassidy.
Keywords: Assassins -- Fiction; Suspense fiction; Audiobooks